Students’ Level of Understanding of SDN Rejosari Towards Bullying in School - Abdur Rohman Zidane Fikri; Nanda Nurul Aulia Tivani; Nur Ufairah; Lusiana Maulida; Amalia Zulfa; Rita Ariyana Nur Khasanah (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to analyze the level of understanding of the students of SDN Rejosari about bullying through direct socialization or counseling and measurement using interviews and questionnaires. The type of research used is qualitative research, which focuses on data acquisition through open communication and conversation. The research was conducted on students in grades 4, 5, and 6 through a socialization or counseling method about bullying. The results showed that 97.6% of students (82 students) understand the concept of bullying thoroughly, while 2.4% (2 students) were included in the category of not understanding. Students' answers during the seminar that are relevant and appropriate show that most students understand the material that has been presented. This data indicates the success of the counseling program in increasing student awareness about bullying. However, additional attempts are needed to improve the understanding of students who do not understand the material well